Novel n‐p‐n heterojunction of AgI/BiOI/UiO‐66 composites with boosting visible light photocatalytic activities. (17th March 2021) - Zhu, Min; Chen, Huimin; Dai, Yu; Wu, Xuanyu; Han, Zhiguo; Zhu, Yu
Abstract : Antibiotics, considered as persistent organic pollutants, have harmful effect on the environment and human health. We aimed at designing and fabricating ternary AgI/BiOI/UiO‐66 composites and evaluate the photocatalytic activities of tetracycline (TC) in water environment under visible light irradiation. X‐ray diffractometer (ХRD), scanning electron microscopy–energy dispersive X‐ray spectroscopy (SEM‐EDS), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET), and ultraviolet–visible (UV‐vis) diffuse reflectance spectra (DRS) analyses were carried out to characterize the ternary AgI/BiOI/UiO‐66 composites. The effects of pristine BiOI, UiO‐66, and AgI loading ratios on the AgI/BiOI/UiO‐66 composites for TC photodegradation were evaluated to obtain the optimal one (1‐ABU ), which can remove 90.1% TC with visible light irradiation. In the batch experiment, the influences of pH, ion strength, TC concentration, and dosage of photocatalyst were investigated. 1‐ABU exhibited excellent photocatalytic activities and stability including pH and ion strength resistance in certain degree. After recycled five times, 1‐ABU still showed good degradation efficiency, indicating the advanced stability of the ternary composites. ·OH and h + active species are the prime, whereas ·O2 − act as secondary during the TC degradation process. 1‐ABU exhibits an n‐p‐n heterojunction, which can inhibit the recombination of photogenerated electron–hole pairs and generate more active ·OH species. This work highlights a reference for the design and synthesis of heterojunction for excellent photocatalytic performance. Abstract : In this work, novel semiconductor composites of AgI/BiOI/UiO‐66 composites were first prepared through the facile solvothermal approach via coating AgI on the surface of BiOI/UiO‐66. AgI/BiOI/UiO‐66 composites exhibit the higher TC photocatalytic degradation under visible light irradiation, which can be attributed to the n‐p‐n heterojunction which can generate more active ·OH species and promote high separation of photogenerated electrons and holes.